Assessing landscape response to tectonics in the Jalisco block and adjacent areas (west-central Mexico) using topographic analysis. (March 2020) - Godínez-Tamay, Arturo; Castillo, Miguel; Ferrari, Luca; Ortega-Gutiérrez, Fernando
Abstract: To elucidate how landscapes respond to either tectonic and climatic changes through time, geomorphologists use the analysis of river and basin morphometry. Many studies have evaluated how rivers, and consequently hillslopes, respond to changes in the rate of rock uplift in compressional settings. The case of extensional settings, however, has received less attention. We examine the case of landscape response to tectonics in west-central Mexico to identify zones where there is notable increase in the tectonic activity. The study of west-central Mexico is challenging for the morphometric analysis since there is an interplay between the development of extensional structures and pulses of volcanism, mainly from Eocene to Oligocene and Pliocene to Pleistocene, that have buried large parts of the landscape. For our purpose we use the normalized channel steepness index ( k sn ) to evaluate how this index correlates with other morphometric parameters such as the hillslope gradient, hillslope convexity and concavity, terrain rugosity and first order stream gradient (Fosg). We use the landform units map as the spatial unit of analysis and from this, we estimate the morphometric properties of the landscape. The results of the morphometric analysis indicate that the topography of Eocene to Oligocene volcanic landscapes are well explained ( 70%) by the k sn and in less degree for Pliocene to Pleistocene landscape where k sn accounts for 55–66% of landscape morphometry. Our results also indicate that the k sn is the best suited among all morphometric variables used in this study and confirm that the landscape of west-central Mexico is dominated by river incision. Landscape incision is particularly high on the northern part of the Jalisco block, mainly along the Ameca river and its tributaries such as Atenguillo river, and north of the Jalisco block, along the Santiago river and on tributaries incising the Sierra Madre Occidental. Finally, the morphometric analysis indicates that even for the case where the volcanic rocks and sediments are filling up large parts of the landscape, river incision resulting from the tectonic activity is capable to cut into lavas, propagating the change imposed by the tectonic activity. Highlights: River incision resulting from tectonic activity dominates in west-central Mexico. River response to tectonics is traceable on volcanic covered landscapes. Landform mapping is useful for the analysis of tectonically active landscapes. The k sn is a robust indicator of tectonic activity over other morphometric indexes.